Clinical Responses of Oncolytic Coxsackievirus A21 (V937) in Patients With Unresectable Melanoma. Issue 34 (1st December 2021) - Andtbacka, Robert H. I.; Curti, Brendan; Daniels, Gregory A.; Hallmeyer, Sigrun; Whitman, Eric D.; Lutzky, Jose; Spitler, Lynn E.; Zhou, Karl; Bommareddy, Praveen K.; Grose, Mark; Wang, Meihua; Wu, Cai; et al.
Abstract : PURPOSE: We evaluated the activity of intratumoral Coxsackievirus A21 (V937) in 57 patients with unresectable stage IIIC or IV melanoma. PATIENTS AND METHODS: In this multicenter, open-label, phase II study, patients received up to a total V937 dose of 3 × 10 8 TCID50 (50% tissue culture infectious dose) in a maximum 4.0-mL volume by intratumoral injection. Ten sets of V937 injections were administered between days 1 and 127 (NCT01227551 ). Patients who had stable disease or were responding could continue treatment in an extension study (NCT01636882 ). Response and progression status were based on contrast-enhanced computed tomography, magnetic resonance imaging, or caliper measurement and were categorized using immune-related Response Evaluation Criteria in Solid Tumors (irRECIST). Other evaluations included monitoring of adverse events and serum levels of V937 and anti-V937 antibody titers. The primary efficacy end point was 6-month progression-free survival (PFS) rate per irRECIST. RESULTS: The primary efficacy end point, 6-month PFS rate per irRECIST, was 38.6% (95% CI, 26.0 to 52.4). Durable response rate (partial or complete response for ≥ 6 months) was 21.1% per irRECIST. Best overall response rate (complete plus partial response) was 38.6% (unconfirmed) and 28.1% (confirmed) per irRECIST. Regression of melanoma was observed in noninjected lesions. Based on Kaplan-Meier estimation, 12-month PFS was 32.9% (95% CI, 19.5 to 46.9) per irRECIST and 12-month overall survival was 75.4% (95% CI, 62.1 to 84.7). No treatment-related grade ≥ 3 adverse events occurred. Viral RNA was detected in serum within 30 minutes of administration. Neutralizing antibody titers increased to > 1:16 in all patients after day 22, without effect on clinical or immunologic response. CONCLUSION: V937 was well tolerated and warrants further investigation for treatment of patients with unresectable melanoma. Studies of combination approaches with V937 and immune checkpoint inhibitors are ongoing. Abstract :